Skrining fitokimia dan uji aktivitas antioksidan dari ekstrak etanol daun kedondong (Spondias dulcis Soland. ex Forst. fil) dengan metode DPPH - Yanti, Rahma; Nasution, Muhammad Amin; Ridwanto, Ridwanto; Nasution, Haris Munandar (Journal of Pharmaceutical and Sciences, 2023)
Antioxidants are compounds that can ward off free radicals and prevent damage caused by free radicals. Free radicals are unstable and reactive molecules formed from unpaired electrons that can cause damage to the skin. To protect the body's skin from free radicals, it can be overcome by using an antioxidant compound. One is kedondong leaves, which contain polyphenolic compounds known to have antibacterial and antioxidant properties. This study aimed to conduct phytochemical screening and determine the antioxidant activity of ethanol extract of kedondong leaves with the DPPH method. This study was conducted experimentally, where the sample used was kedondong leaves. The stages of research include sample preparation, plant identification, making simplisia, phytochemical screening on kedondong leaf extract and simplisia, then antioxidant activity tests were carried out on kedondong leaf ethanol extract using the DPPH method (1,1-diphenyl -2-picrylhydrazil) at a maximum wavelength of 516 nm, as a positive control vitamin C was used. The research on phytochemical screening showed that ethanol extract of kedondong leaves contains secondary metabolite compounds, namely tannins, saponins, alkaloids, flavonoids, steroids, triterpenoids, and glycosides. In testing, the antioxidant activity of ethanol extract of kedondong leaves showed very strong antioxidant activity with an IC50 of 44.855 μg/ml, and vitamin C had very strong antioxidant activity with an IC50 of 4.44 μg/ml.